HUBUNGAN KONSTITUSI DENGAN TUGAS DAN FUNGSI NEGARA - Mu'allifin, M. Darin Arif (IAIN Tulungagung, 2016)
A state’s constitution basically is a promise to be fulfilled. It has animportant role in a state’s life cycle. In management, constitutionis considered as a system which functions as law planning, laworganizing, law actuating, and law controlling to achieve the state’sideals and objectives. Because of its fundamental role, when a systemicproblem occurs, constitution reform, institution reform, and culturalreform can be a choice to solve the problem.Kata kunci: Konstitusi, Reformasi, Institusi